PENGARUH EKONOMI TERHADAP KESUKSESAN ULAMA HADIS - Roy Grafika Penataran; Sylvano Wijaya Aji Pratama; Rizki Fajar Ramdani (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
Everyone wants success. To achieve it, there are many supporting factors. Some can run well, but some can become obstacles. The success of the hadith scholars also do not escape from those obstacles. The economic factor is an example of their obstacles. However, they do not make it as a problem in thier study. From those different economic factors which make them success, it then creates some questions. How are their condition in their studies? Is economic condition a problem? What are the evidences, so they are said to be successful? And what are the factors that make them success? In this study, the author tries to find the authentic sources in tracing their lifes in trusted books, so the authors find that the economy is not an obstacle for them. Their success was also obtained from several factors including the recognition of the scholars, the book they wrote, the success factors in the Diwan Al Imam Al-Shafi'i, the piety and the support from their closest people.